AB0335 Effect of total knee arthroplasty on medication in patients with rheumatoid arthritis. (15th June 2017) - Harigane, K; Mochida, Y; Kumagai, K; Ishii, K; Miyamae, Y; Mitsugi, N; Choe, H; Nagaoka, A; Inaba, Y; Saito, T
Abstract : Background: Several studies reported that development of phaemacological treatment for rheumatoid arthritis (RA) contributed to decreased number of orthopaedic surgery. [1–3] Surgical treatment is, however, still required in many cases, and the impact of orthopaedic surgery on disease activity remain unclear. Objectives: This study evaluated the effect of total knee arthroplasty (TKA) with capsulosynovectomy on chenges of disease activity and medication in patients with RA. Methods: Seventy-seven serial patients with RA (61 female and 16 male) who underwent primary TKA with more than one year of follow-up were retrospectively reviewed to assess postoperative disease activity and drug administration. The mean age at the time of surgery was 68.3 years old. The disease activity of RA was measured using Disease Activity Score in 28 Joints (DAS28). To evaluate the effects of medication on preoperative and postoperative disease activity, outcomes at before surgery and one year after surgery were separately investigated following two groups; patients who were treated with the same or reduced medication (same group) and patients who were administered with additional or altered medication (change group). Results: Seventy-two patients (97.3%) were administered with at least one DMRDs before or after surgery. The mean dose of methotrexate (MTX) was 7.7mg/week before surgery and 8.0mg/week after surgery respectively. The number of patients who were treated with biological DMARDs was increased after surgery (17 patients vs.21 patients), however there was not significant differences. RA disease activity was significantly decreased in DAS28-CRP one year after surgery. (3.9 vs. 2.7, p<0.01) As for difference of the disease activity in same and change groups, DAS28-CRP was significantly decreased after surgery. (same group; 3.7 vs. 2.5, p<0.01, change group; 4.5 vs. 3.2, p<0.01) DAS28-CRP in change group was significantly higher both before and after surgery compared with those in same group. (p<0.01) Conclusions: TKA with capsulosynovectomy improves disease activity after surgery in patients with RA. Based on the results, patients with higher disease activity before surgery required further medication after surgery. References: Dusad A et al. Impact of Total Knee Arthroplasty as Assessed Using Patient-Reported Pain and Health-Related Quality of Life Indices: Rheumatoid Arthritis Versus Osteoarthritis. Arthritis Rheumatol. 2015; 67: 2503–11. Yano K et al. Effect of total knee arthroplasty on disease activity in patients with established rheumatoid arthritis: 3-year follow-up results of combined medical therapy and surgical intervention. Mod Rheumatol. 2010; 20: 452–7. Oh K et al. Effects of surgical intervention on disease activity of rheumatoid arthritis: cases of surgery for rheumatoid arthritis of the lower limbs treated with biologics. Mod Rheumatol. 2014; 24: 606–11. Disclosure of Interest: None declared